The Characteristics of Lahar in Merapi Volcano, Central Java as the Indicator of the Explosivity during Holocene - Adjat Sudradjat; Ildrem Syafri; E. T. Paripurno (Geological Agency, 2011)
DOI: 10.17014/ijog.v6i2.116Merapi Volcano in Central Java has been the most active volcano during Holocene time. As a strato volcano, Merapi exhibits alternating volcanic activities of effusive and explosive characters and self destruction. The explosivity index has evolved during the last ten thousand years. The effusive activities were characterized by the occurrence of lava flows, the development of lava dome, and the production of the “nuee ardente d’avalanche” called Merapi type. The explosive stage is frequently accompanied by the occurence of pyroclastic flows. The present investigation is attempted to reveal the relationship between the characteristics of lahar and the evolution of the activity of Merapi Volcano. The quantitative analysis was focused on the size and shape of the lahar components particularly that of pumice as the main indicators in 73 measured stratigraphic columns of lahar deposits. In addition, the main chemical element rim structures of hornblende identified in lahar components indicate the different lahar units. There are five lahar units and five groups of Merapi activities which can be distinguished. It can be concluded that the characteristics of lahar reflect the evolution of the activities in the past. The risk analyses of Merapi Volcano therefore can be enlarged to cover the possible hazard based on the lahar characteristics.